2018
DOI: 10.1097/brs.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Field-of-View Diffusion Tensor Imaging of the Spinal Cord Shows Motor Dysfunction of the Lower Extremities in Patients With Cervical Compression Myelopathy

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Among these studies, the majority (38/67, 57%) only investigated correlations with a single coarse clinical measure, such as Expanded Disability Status Scale (EDSS), Japanese Orthopedic Association (JOA), modified JOA (mJOA), amyotrophic lateral sclerosis (ALS) Functional Rating Scale (ALSFRS), or ASIA Impairment Scale (AIS), rather than employing a battery of assessments or using more detailed measures of impairment such as ASIA motor/sensory scores. The majority of DTI studies reporting biomarker utility results focused on the metric FA, which was particularly successful in CSM with significant results in 5/5 studies correlating with JOA or mJOA (Spearman r = 0.48–0.88, Pearson R = 0.57–0.64) ( Ellingson et al, 2014 , Gao et al, 2013 , Jones et al, 2013 , Maki et al, 2015 , Wen et al, 2014b ) and in SCI in 4/4 studies correlating with ASIA motor/sensory scores (r = 0.59–0.74, R = 0.78–0.92) ( Cheran et al, 2011 , Cohen-Adad et al, 2011 , Koskinen et al, 2013 , Vedantam et al, 2015 ), but slightly less successful in MS with significant results in only 7/15 studies correlating with EDSS (r = − 0.37–0.51, R = − 0.60) ( Agosta et al, 2007a , Benedetti et al, 2010 , Naismith et al, 2013 , Oh et al, 2013a , Oh et al, 2013b , Toosy et al, 2014 , Valsasina et al, 2005 ), with negative results in 8 studies ( Agosta et al, 2005 , Ciccarelli et al, 2007 , Hodel et al, 2013 , Miraldi et al, 2013 , Oh et al, 2015 , Raz et al, 2013 , Rocca et al, 2012 , Ukmar et al, 2012 ). Other metrics had limited success in MS correlating with EDSS, with significant results for MD in 3/13 studies ( Oh et al, 2013a , Oh et al, 2013b , Valsasina et al, 2005 ), RD in 4/8 studies ( Naismith et al, 2013 , Oh et al, 2013a , Oh et al, 2013b , Toosy et al, 2014 ), MTR in 6/15 studies ( Agosta et al, 2007b , Bozzali et al, 1999 , Kearney et al, 2014 , Lycklama et al, 2000 , Oh et al, 2013a , Oh et al, 2013b ), MTCSF in 2/2 studies ( Fatemi et al, 2005 , Zackowski et al, 2009 ), and the ...…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, the majority (38/67, 57%) only investigated correlations with a single coarse clinical measure, such as Expanded Disability Status Scale (EDSS), Japanese Orthopedic Association (JOA), modified JOA (mJOA), amyotrophic lateral sclerosis (ALS) Functional Rating Scale (ALSFRS), or ASIA Impairment Scale (AIS), rather than employing a battery of assessments or using more detailed measures of impairment such as ASIA motor/sensory scores. The majority of DTI studies reporting biomarker utility results focused on the metric FA, which was particularly successful in CSM with significant results in 5/5 studies correlating with JOA or mJOA (Spearman r = 0.48–0.88, Pearson R = 0.57–0.64) ( Ellingson et al, 2014 , Gao et al, 2013 , Jones et al, 2013 , Maki et al, 2015 , Wen et al, 2014b ) and in SCI in 4/4 studies correlating with ASIA motor/sensory scores (r = 0.59–0.74, R = 0.78–0.92) ( Cheran et al, 2011 , Cohen-Adad et al, 2011 , Koskinen et al, 2013 , Vedantam et al, 2015 ), but slightly less successful in MS with significant results in only 7/15 studies correlating with EDSS (r = − 0.37–0.51, R = − 0.60) ( Agosta et al, 2007a , Benedetti et al, 2010 , Naismith et al, 2013 , Oh et al, 2013a , Oh et al, 2013b , Toosy et al, 2014 , Valsasina et al, 2005 ), with negative results in 8 studies ( Agosta et al, 2005 , Ciccarelli et al, 2007 , Hodel et al, 2013 , Miraldi et al, 2013 , Oh et al, 2015 , Raz et al, 2013 , Rocca et al, 2012 , Ukmar et al, 2012 ). Other metrics had limited success in MS correlating with EDSS, with significant results for MD in 3/13 studies ( Oh et al, 2013a , Oh et al, 2013b , Valsasina et al, 2005 ), RD in 4/8 studies ( Naismith et al, 2013 , Oh et al, 2013a , Oh et al, 2013b , Toosy et al, 2014 ), MTR in 6/15 studies ( Agosta et al, 2007b , Bozzali et al, 1999 , Kearney et al, 2014 , Lycklama et al, 2000 , Oh et al, 2013a , Oh et al, 2013b ), MTCSF in 2/2 studies ( Fatemi et al, 2005 , Zackowski et al, 2009 ), and the ...…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review of the literature 59 identified a total of 25 studies that used these techniques to study DCM; 22 used DTI, 3 used MRS, and 1 used MT (in combination with DTI). 10,17,21,22,24,25,30,35,36,39,46,52,53,55,56,58,73,93,104,112,116,124,125,129,136 No clinical studies that used MWF or fMRI were identified. Among the identified DCM studies, the DTI metric fractional anisotropy (FA), a number that ranges from 0 for isotropic diffusion (same in all directions) to 1 for anisotropic (all in 1 direction), seemed to have the strongest results.…”
Section: Studies Using Advanced Mri In Dcmmentioning
confidence: 99%
“…rFOV DTI of the spinal cord allows for acquisition of high-resolution images for assessment of specific spinal cord tracts and discrimination of white matter from gray matter. Maki et al 72) showed correlations between the FA of specific white matter in spinal cord tracts and myelopathy severity in …”
Section: Future Directions; High-resolution Dtimentioning
confidence: 99%